An adolescent with Hodgkin Lymphoma Health Seeking Behaviour and the Primary Health Care Response - Ain Mohd Noor, Noor Faridzatul; Rashid, Aneesa Abdul (International Journal of Human and Health Sciences (IJHHS), 2023)
Hodgkin lymphoma (HL) accounts for approximately 10 percent of all lymphomas. HL is a type of lymphoma that accounts for around 7% of childhood cancers. Lymphoma is a rare form of cancer that must be diagnosed and treated immediately for a better outcome. This case study illustrates how a 17-year-old adolescent and his family battled a sickness that they had never heard of before. He presented with severe cough and systemic symptoms including night sweats, weight loss or fever. On his physical examination, there was no palpable peripheral lymphadenopathy. The biochemical results showed increased c-reactive protein and a neutrophilic leukocytosis of approximately 15,500 leukocytes per microliter. Chest radiograph revealed a significant left-sided pleural effusion and a large mediastinal mass measuring 10 cm. He was screened for tuberculosis at the health clinic and found to be normal findings. To accelerate diagnostic procedures, the patient was admitted to the internal medicine department. Chest Computed Tomography showed a large anterior mediastinal mass, causing effect and compression onto adjacent great vessels and left the main bronchus, associated with moderate left pleural effusion, as confirmed by histopathology findings. Although HL is mainly managed in a hospital setting, primary care plays a vital role in this study; the importance of recognizing patients with social-related problems, such as financial constraints or logistic issues to avoid this becoming a barrier to seeking treatment in health care facilities. This case commentary discusses the delay in identifying such a high-risk patient at the primary care level, who was later diagnosed with HL. Essential role through effective education, supportive care, and symptom management, can play an important role to help them make the right decision in obtaining healthcare services and further treatment for a better outcome. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S32